Metropolises - the Contemporary Challenge to Local Governments - Monika Augustyniak (Bratislava Law Review, 2023)
Metropolisation is a process that includes the consequences of global phenomena transferred to the level of metropolitan areas, being the result of various legal and social processes, which is best illustrated by the example of French and Polish institutional solutions. France has been chosen to perform the analysis on due to the uniqueness of its legal regulations in the field of the issues covered in the study (e.g., the institution of metropolitan poles [le pôle métropolitain]). The possibility of creating a metropolis in its current form has existed in France since 2010, but the legislative bodies are still introducing changes to strengthen the legal position of this institution. The French legal order continues to reinforce the role and importance of the metropolis as a unit of inter-municipal cooperation that can take over the department and region’s essential competences to manage the metropolitan area more effectively. In a sense, France is becoming a model of organisation and functioning for contemporary metropolises in Poland, which are beginning to emerge as a certain remedy to the effectiveness issue of performing supra-regional tasks. This article provides an analysis of the law as it stands for legal regulations concerning the organisation and functioning of metropolises both in France and Poland in a comparative and legal context, with the aim of making postulates regarding the choice of a right formula for performing tasks in contemporary local governments.